2021
DOI: 10.3390/jcm10235591
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Indices in Identifying Insulin Resistance and Diabetes in Chronic Spinal Cord Injury

Abstract: The purpose of this screening and diagnostic study was to examine the accord among indices of glucose metabolism, including the Homeostatic Model Assessment for Insulin Resistance (HOMA), HOMA2, Matsuda Index, Quantitative Insulin-sensitivity Check Index (QUICKI), hemoglobin A1C (HbA1C), and fasting plasma glucose (FPG) against intravenous glucose tolerance test-measured insulin sensitivity (Si) in individuals with chronic motor complete SCI. Persons with chronic (≥12-months post-injury) SCI (n = 29; 79% men; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Spinal cord injury (SCI) is a severe neurological injury that results in damage to multiple bodily systems and functions. It is often associated with secondary conditions including chronic pain [ 1 , 2 ], spasticity [ 3 ], urinary tract infection [ 4 ], bowel complications [ 5 ], insulin resistance and diabetes [ 6 ], sexual dysfunction [ 7 ], pressure injuries [ 8 ], cardiovascular and respiratory problems [ 9 , 10 ], fatigue [ 11 , 12 ], cognitive impairment, and low vitality/fatigue and mental health problems [ 13 , 14 , 15 , 16 ]. In addition, it can lead to reduced social autonomy [ 17 ] and greater challenges for gaining and sustaining employment [ 18 ], and there exists a high risk of weight gain and sleep disturbance [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a severe neurological injury that results in damage to multiple bodily systems and functions. It is often associated with secondary conditions including chronic pain [ 1 , 2 ], spasticity [ 3 ], urinary tract infection [ 4 ], bowel complications [ 5 ], insulin resistance and diabetes [ 6 ], sexual dysfunction [ 7 ], pressure injuries [ 8 ], cardiovascular and respiratory problems [ 9 , 10 ], fatigue [ 11 , 12 ], cognitive impairment, and low vitality/fatigue and mental health problems [ 13 , 14 , 15 , 16 ]. In addition, it can lead to reduced social autonomy [ 17 ] and greater challenges for gaining and sustaining employment [ 18 ], and there exists a high risk of weight gain and sleep disturbance [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Solinsky et al [ 84 ] identified insulin resistance in 12.5% of their cohort using elevated fasting plasma glucose as a criterion but in 33.3% when using Homeostatic Model Assessment 2 for Insulin Resistance (HOMA2-IR) criteria. Farkas and colleagues [ 125 ] recently examined the accord among indices of glucose metabolism against the gold standard measure of insulin sensitivity as assessed by the intravenous glucose tolerance test in 29 people with chronic motor complete SCI (79% men, 42.2 ± 11.4 years old, BMI 28.6 ± 6.4 kg/m 2 , C4 to T10). The authors demonstrated that the greatest agreement with insulin sensitivity was with the Quantitative Insulin-sensitivity Check Index (QUICKI), followed by Homeostatic Model Assessment for Insulin Resistance, HOMA2-IR, and the Matsuda Index.…”
Section: Dysglycemia and Insulin Resistance After Scimentioning
confidence: 99%
“…Despite being commonly used for evaluating disorders of carbohydrate metabolism, fasting plasma glucose and hemoglobin A1C had the poorest agreement with insulin sensitivity. Farkas et al [ 125 ] hypothesized that QUICKI’s superior agreement stems from the log transformation of QUICKI values. The authors noted that for people with SCI, in the absence of QUICKI, fasting plasma glucose and hemoglobin A1C should be used in combination rather than in isolation to provide better diagnostic utility.…”
Section: Dysglycemia and Insulin Resistance After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…The QUICKI is the inverse of the HOMA-IR and assesses insulin sensitivity instead of IR (69) and a value <0.339 indicated IR (59)(60)(61)(62).…”
Section: Research Design Study Population and Inclusion And Exclusion...mentioning
confidence: 99%